Análisis y diagnóstico de la equidad de género en las actividades secretariales de las empresas públicas y privadas de la ciudad de Latacunga - Ramos Casa, Nelson Aníbal (2016)
This research work has as a general objective, to make an analysis and diagnosis of the gender equity of secretarial activities in the public and private enterprises of the city of Latacunga, their influence on gender relations, for which it is important the contribution and the availability of the departments of human talent in public and private companies to be partakers of this research. The methodology has a bimodal approach; applies techniques such as: survey and interview, the Directors of Human talent together with the partners that has each institution….